Diagnosing rheumatic heart disease: where are we now and what are the challenges?. (2nd September 2021) - de Loizaga, Sarah R.; Beaton, Andrea Z.; Nascimento, Bruno R.; Macedo, Frederico Vargas Botinha; Spolaor, Breno Camargos Mucelli; de Pádua, Lucas Bretas; Ribeiro, Thomas Felipe Silva; Oliveira, Guilherme Catizani Faria; Oliveira, Lucas Rocha; de Almeida, Luís Felipe Rezende; Moura, Thomás Diniz; de Barros, Talisson Taglialegna; et al.
ABSTRACT: Introduction: Rheumatic heart disease (RHD), a sequela of acute rheumatic fever (ARF), affects 40.5 million people worldwide. The burden of disease disproportionately falls on low- and middle-income countries (LMIC) and sub-populations within high-income countries (HIC). Advances have been made in earlier detection of RHD, though several barriers to ideal management persist. Areas Covered: This article reviews the current burden of RHD, highlighting the disparate impact of disease. It also reviews the clinical and echocardiographic presentation of RHD, as some may present in late stages of disease with associated complications. Finally, we review the advances which have been made in echocardiographic screening to detect latent RHD, highlighting the challenges which remain regarding secondary prophylaxis management and uncertainty of best practices for treatment of latent RHD. Expert opinion: Advances in technology and validation of portable echocardiography have made screening and identifying latent RHD feasible in the most burdened regions. However, uncertainty remains around best management of those with latent RHD and best methods to ensure ideal secondary prophylaxis for RHD. Research regarding latent RHD management, as well as continued work on innovative solutions (such as group A streptococcal vaccine), are promising as efforts to improve outcomes of this preventable disease persist.